Analisis Penerapan Akuntansi Syariah Berdasarkan PSAK 102 pada Pembiayaan Murabahah di BMT Bina Insan Sejahtera - Wati, Zahra; Rosmanidar, Elyanti; Budianto, Achyat (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims To find out the murabahah financing mechanism at BMT Bina Insan Sejahtera and To analyze the recognition, measurement, presentation and disclosure of murabahah transactions based on PSAK 102 at BMT Bina Insan Sejahtera. This research uses qualitative methods with research data obtained through interviews and documentation by taking sources from the administrators, managers and customers of BMT Bina Insan Sejahtera. The data analysis used in this research is a qualitative descriptive technique. The results of this research show that only a small part of the murabahah bookkeeping treatment carried out by BMT Bina Insan Sejahtera is in accordance with PSAK 102. However, there are several things that are not in accordance with PSAK 102, namely BMT Bina Insan Sejahtera's practice of not keeping journals or no accounting treatment regarding money. face, the presentation of murabahah receivables is not yet in accordance with PSAK 102, and the presentation of financial statements is not fully in accordance with PSAK 102.